2019
DOI: 10.1002/adsu.201900027
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Organic Dyes as Molecular Photocatalysts for H2O2 Evolution

Abstract: cousin H 2 . To its advantage, H 2 O 2 forms stable aqueous solutions, [8] and does not require compression and storage as gaseous H 2 does. Photocatalytic evolution of peroxide has proven to be more selective than CO 2 reduction, [9] giving only one product. What is more, the energy accumulated in H 2 O 2 can be utilized directly for electricity generation in a membranefree hydrogen peroxide fuel cell (theoretical V oc = 1.1 V, comparable with the 1.23 V of H 2 fuel cells), which can be made as a single-compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…2b and c). Based on our previously published results on peroxide-evolving dyes 16 in solution we would maintain that it is most probable that both for lignin and LS the reaction mechanism proceeds via single-electron reduction of oxygen to superoxide, which subsequently disproportionates to form stable hydrogen peroxide. Such a mechanism is kinetically most facile, however a contribution from concerted two-electron/two-proton reduction of oxygen to peroxide cannot be ruled out.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2b and c). Based on our previously published results on peroxide-evolving dyes 16 in solution we would maintain that it is most probable that both for lignin and LS the reaction mechanism proceeds via single-electron reduction of oxygen to superoxide, which subsequently disproportionates to form stable hydrogen peroxide. Such a mechanism is kinetically most facile, however a contribution from concerted two-electron/two-proton reduction of oxygen to peroxide cannot be ruled out.…”
Section: Resultsmentioning
confidence: 96%
“…1 These demands motivated us to explore the possibility of peroxide evolution catalyzed by abundant biomaterials. The present study was guided by recent findings that organic carbonyl dyes 16 and pigments 17 as well as the structurally-related biopolymer eumelanin 18 are photocatalysts for selective reduction of oxygen to peroxide. Lignin shares critical structural features with these proven catalytic speciesnamely aromatic conjugated units with quinone/ hydroquinone redox moieties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In this context, organic photocatalysts that operate in aqueous solvents have been the focus of considerable recent interest as sustainable alternatives to conventional photocatalysts. [10][11][12][13][14] To date, these photocatalysts/photosensitizers are primarily porphyrin-based, and their photocatalytic applications are mostly limited to water-soluble substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen reduction reactions, on the other hand, have been discovered to be highly favored on organic semiconductors (Bellani et al, 2015). The single-electron reduction of O 2 to superoxide (Suppes et al, 2013;Gryszel et al, 2019) or the two-electron reduction to produce hydrogen peroxide (Jakešová et al, 2016;Węcławski et al, 2017;Gryszel et al, 2018b), H 2 O 2 , were demonstrated to proceed efficiently for several organic semiconductors. Both oxygen reduction reactions are thermodynamically more favorable than hydrogen evolution, with the two-electron peroxide reaction being 700 mV lower than H 2 production.…”
Section: Photochemical Reactionsmentioning
confidence: 99%